G.I.S. Surveillance of Chronic Non-occupational Exposure to Heavy Metals as Oncogenic Risk - Mariana Vlad; Cecilia Roman; Ioana Brie; Ioan Stelian Bocşan; Irina Brumboiu; Tudor Călinici; Mihaela Lucia Ponta (AIMS Press, 2016)
Introduction: The potential oncogenic effect of some heavy metals in people occupationally and non-occupationally exposed to such heavy metals is already well demonstrated. This study seeks to clarify the potential role of these heavy metals in the living environment, in this case in non-occupational multifactorial aetiology of malignancies in the inhabitants of areas with increased prevalent environmental levels of heavy metals. Methods: Using a multidisciplinary approach throughout a complex epidemiological study, we investigated the potential oncogenic role of non-occupational environmental exposure to some heavy metals [chrome (Cr), nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd), lead (Pb) and arsenic (As)-in soil, drinking water, and food, as significant components of the environment] in populations living in areas with different environmental levels (high vs. low) of the above-mentioned heavy metals. The exposures were evaluated by identifying the exposed populations, the critical elements of the ecosystems, and as according to the means of identifying the types of exposure. The results were interpreted both epidemiologically (causal inference, statistical significance, mathematical modelling) and by using a GIS approach, which enabled indirect surveillance of oncogenic risks in each population. Results: The exposure to the investigated heavy metals provides significant risk factors of cancer in exposed populations, in both urban and rural areas [χ² test (p < 0.05)]. The GIS approach enables indirect surveillance of oncogenic risk in populations. Conclusions: The role of non-occupational environmental exposure to some heavy metals in daily life is among the more significant oncogenic risk factors in exposed populations. The statistically significant associations between environmental exposure to such heavy metals and frequency of neoplasia in exposed populations become obvious when demonstrated on maps using the GIS system. Environmental surveillance of heavy metals pollution using GIS should be identified as an important element of surveillance, early detection, and control of neoplastic risks in populations, at the level of a single locality, but even on a wider geographical scale.